2013
DOI: 10.1175/wcas-d-12-00007.1
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits and Challenges of Predictive Interval Forecasts and Verification Graphics for End Users

Abstract: Two behavioral experiments tested the use of predictive interval forecasts and verification graphics by nonexpert end users. Most participants were able to use a simple key to understand a predictive interval graphic, showing a bracket to indicate the upper and lower boundary values of the 80% predictive interval for temperature. In the context of a freeze warning task, the predictive interval forecast narrowed user expectations and alerted participants to the possibility of colder temperatures. As a result, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Graphical displays of variability and probability have in other studies been shown to improve probabilistic judgments (e.g., in the area of health risks) and bring them more in line with formal requirements (Burkell, 2004;Joslyn et al, 2013;Lipkus and Hollands, 1999)…”
Section: Discussionmentioning
confidence: 99%
“…Graphical displays of variability and probability have in other studies been shown to improve probabilistic judgments (e.g., in the area of health risks) and bring them more in line with formal requirements (Burkell, 2004;Joslyn et al, 2013;Lipkus and Hollands, 1999)…”
Section: Discussionmentioning
confidence: 99%
“…But will enough people be able to understand the verification? Despite the fact that this information is both abstract and complex, there is some preliminary evidence suggesting that non-experts can understand simple verification graphics for both deterministic and probabilistic forecasts (Joslyn et al ., 2013). With no explicit training, using only a simple key, college undergraduates were readily able to identify forecasts that performed better over various forecast periods.…”
Section: User-oriented Verificationmentioning
confidence: 99%
“…In theory, a range of values and the associated probability provide useful uncertainty information to both. Indeed, research with college student participants suggests that predictive intervals benefit users in just that way, allowing them to better distinguish, than do point estimates, situations in which to take precautionary action [12,13]. In these studies, some participants based their decisions on a forecast that included the upper and lower bound temperatures for an 80% predictive interval as well as a median value described at the "most likely" temperature.…”
Section: Introductionmentioning
confidence: 99%